Acoustic Telemetry Around Western Australia’s Oil and Gas Infrastructure Helps Detect the Presence of an Elusive and Endangered Migratory Giant - Thomson, Paul G.; Pillans, Richard; Jaine, Fabrice R. A.; Harcourt, Robert G.; Taylor, Michael D.; Pattiaratchi, Charitha B.; McLean, Dianne L. (Frontiers in Marine Science, 2021)
Subsea infrastructure of the oil and gas industry attracts commercial fish species as well as megafauna including sea lions, turtles, sharks and whales. Potential impacts of this attraction, whether positive or negative, are unknown. As part of a pilot study, we deployed acoustic telemetry equipment around offshore infrastructure to assess its effectiveness in detecting tagged marine animals and to gain insights into patterns of megafauna occurrence around these structures. Acoustic receivers were placed around four oil and gas platforms and on two remotely operated vehicles (ROVs) on Australia’s North West Shelf. Two whale sharks (Rhincodon typus) tagged in the World Heritage Ningaloo Reef Marine Park were detected at two platforms, North Rankin A and Pluto, located up to 340 km to the northeast. The shark at North Rankin A was detected infrequently and only 15 times over ∼6 weeks. The shark at Pluto was detected each day of the 24-day deployment, in total 4,894 times. Detections at Pluto platform were highest during the day, with peaks at dusk and dawn. Our study indicates that acoustic telemetry around platforms may be an effective method for understanding how marine megafauna utilise these structures. We recommend collaborating with industry to undertake receiver detection range testing to understand the effectiveness of the method. Furthermore, future studies should co-occur with tagging programs at sites like Ningaloo Reef and around the structures themselves to maximise the probability of detecting animals at these sites, thereby improving our understanding of how marine megafauna interact with these structures.